Satisfacción y calidad de vida en pacientes intervenidos quirúrgicamente de cirugía herniaria inguinal primaria en dos hospitales de la Amazonía Peruana – 2023 - Echemendia Miller, Fernando (2024)
This article describes a study on the satisfaction and quality of life of patients undergoing primary inguinal hernia surgery in hospitals in Peru. The objective is to evaluate satisfaction and quality of life after surgery and analyze the sociodemographic and surgery-related factors that influence these aspects. The study builds on previous research that has shown that inguinal hernia is a major public health problem that can affect patient quality of life and satisfaction. Inguinal hernia surgery is a common procedure, but there are deficiencies in medical care that limit access to timely diagnosis and treatment. The study seeks to determine the level of quality of life and satisfaction of patients undergoing primary inguinal hernia surgery at the Regional Hospital of Loreto and Hospital III Essalud Iquitos in 2023. It also seeks to identify the sociodemographic and surgery-related factors that influence patient satisfaction and quality of life. The background of similar studies conducted in other countries will be reviewed. These studies have shown that the surgical technique used, recovery time, and the presence of complications can influence patient satisfaction and quality of life after inguinal hernia surgery. The study will use specific surveys and scales to assess patient satisfaction and quality of life.